Orthogonal Analysis of Axial Bearing Capacity of Long Columns Reinforced by Circular Steel Tube and Ultra High Performance Concrete with Coarse Aggregate - Zhang, Weidong; Zhu, Guanyu; Tang, Jiajun (Scientific Journal of Technology, 2026)
The influence of steel pipe wall thickness, steel pipe length, ultra high performance concrete with coarse aggregate (UHPC-CA) strength, and steel grade on the axial compressive bearing capacity of round steel pipe UHPC-CA long columns was analyzed using orthogonal experimental method. The results indicate that the influence of various factors on the axial compressive bearing capacity of round steel tube UHPC-CA long columns is in the order of steel grade>steel tube wall thickness>steel tube length>UHPC-CA strength. The axial compressive bearing capacity increases with the increase of steel pipe wall thickness, UHPC-CA strength, and steel grade, and decreases with the increase of steel pipe outer diameter. When the aspect ratio is 8 and 10, the axial compressive bearing capacity increases with the increase of the hoop coefficient. When the aspect ratio is 12, the axial compressive bearing capacity first decreases and then increases with the increase of the hoop coefficient.